Contributions of diet quality and diapause duration to the termination of larval diapause in khapra beetle, Trogoderma granarium (Coleoptera: Dermestidae). (January 2020) - Shivananjappa, S.; Fields, P.; Laird, R.A.; Floate, K.D.
Abstract: Larvae of khapra beetle, Trogoderma granarium (Coleoptera: Dermestidae) have an unusual diapause during which they may sporadically feed for several years, but not complete development. Diapausing larvae have an enhanced tolerance to starvation, insecticides and extreme temperatures. Thus, knowledge of factors that terminate larval diapause may aid in the control of this pest. In the current study, we assessed the effect of diet quality (five mixtures of fresh and spent diet in a replacement series) on diapause termination for diapausing larvae from laboratory cultures aged 3, 10, or 14 months. Larvae ( n = 10 replicates for each combination of diet quality and culture, 10 larvae/replicate) were held at 30 °C and observed at different intervals over the course of 188 days to record larval mortality and larval pupation (= diapause termination). Larvae were least able to survive on diets of lower quality; i.e., 88% mortality after 188 days on 0% fresh diet versus 8% mortality on 100% fresh diet (averaged across cultures). Larvae were most likely to terminate diapause on diets of higher quality; i.e., 87% termination after 188 days on 100% fresh diet versus 0% termination on 0% fresh diet (averaged across cultures). Diapausing larvae from older cultures were least likely to terminate diapause and least likely to survive. On 100% fresh diet, diapause termination of larvae from cultures aged 3, 10 and 14 months was 93, 91, and 78%, respectively. On 0% fresh diet, mortality of larvae from cultures aged 3, 10 and 14 months was 67, 97, and 100%, respectively. These results indicate that diapausing larvae can accumulate the nutrients required to terminate diapause and complete development when provided with an opportunity to do so. However, the window of opportunity continues to shrink the longer the larvae remain in diapause. Highlights: Khapra beetle, Trogoderma granarium, diapause as late-instar larvae. Diapausing larvae are more likely to break diapause on diets of higher quality. Diapausing larvae are more likely to survive on diets of higher quality. Larvae are less likely to break diapause the longer that they remain in diapause. The longer that larvae remain in diapause, the more likely they are to die.